Oral health-related quality of life among students of the Medical University in the Russian Arctic - Popov, VA; Vyborova, PS; Gordienko, AA; Moseev, RI; Yushmanova, TN; Gorbatova, Maria A.; Drachev, Sergei Nikolaevich (Human Ecology, 2020)
The aim is to assess oral health-related quality of life (OHRQoL) and factors associated with OHRQoL among the students of the medical university. Methods. The cross-sectional study included 308 Russian speaking third year students aged 19-25 years from the Faculty of General Medicine, Paediatrics, Preventive Medicine and Dentistry of the Northern State Medical University (NSMU), Arkhangelsk, Russian Arctic. The Oral Health (OH) Impact Profile (OHIP-14) was used to measure OHRQoL. Information on socio-demographic factors, self-esteem of tooth and gingiva health, OH behaviour, and diet was obtained from the OH Questionnaire for adults (World Health Organization, 2013). Pearson's chi-square test and multivariable Poisson regression with robust estimate of dispersion were used for statistical analysis. Results: 33,8 % and 18,5 % of students had poor dentition and gingiva, respectively. 39,0 % of students consumed sweet pies/buns more than once a week; 39.0 % of students reported on low OHRQoL. The highest mean scores OHIP-14 were found for the dimensions "physical pain" and "psychological discomfort": 1.59 (95 % confidence interval (CI): 1.43-1.75) and 0.84 (95 % CI: 0.70-0.98), respectively. Female sex (prevalence ratio (PR) = 1.73, 95 % CI: 1.23-2.45), poor self-esteem of teeth health (PR = 2.32, 95 % CI: 1.77-3.04), and sweet pies/buns consumption more than once a week (PR = 1.39, 95 % CI: 1.07-1.80), were all significantly and independently associated with low OHRQoL. Conclusions: Relatively high prevalence of low OHRQoL was observed in the examined students. Female sex, poor self-esteem of teeth health and frequent consumption of sweet pies/buns were associated with low OHRQoL. To enhance OHRQoL in Russian students, the preventive strategies for dental diseases and diet improvement should be implemented. Цель: оценить качество жизни, связанное со стоматологическим здоровьем (КЖССЗ), студентов медицинского университета и выявить взаимосвязанные с ним факторы. Методы. В поперечном исследовании участвовали 308 ...